PROJECT IMPLEMENTATION TO STRENGTHEN PANCASILA STUDENT PROFILE AT ACTIVATOR SCHOOL OF SMPIT INSAN MULIA, MANOKWARI REGENCY, WEST PAPUA - Aida, Aida; Budiarti, Indah Slamet; Ompe, Edison; Yulius, Yulius (jfpublisher, 2024)
The Pancasila Student Profile Strengthening Project (P5), which has been implemented by activator schools in Indonesia since 2021, aims to improve the quality of character education. This project guides character education in the Merdeka Curriculum, which is implemented through a positive culture built by schools through intracurricular, co-curricular, and extracurricular learning. This research aims to analyze the whole activity by involving partners and identifying factors that support or hinder the implementation of P5 at SMPIT Insan Mulia, Manokwari Regency, West Papua. This research adopted descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation checking. Data validity was tested using triangulation techniques and discussions with peers, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The P5 implementation at SMPIT Insan Mulia Manokwari began with planning and were followed by socialization to teachers, students, and parents, fostering proactive attitudes and gotong royong. Optimizing P5 according to project guidelines enhanced student engagement through innovative learning, encouraging creativity and critical thinking. Teachers facilitated reflective dialogue to develop a positive school culture. The program concluded with a learning celebration to appreciate students' efforts. Key supporting factors included the principal's role, teacher collaboration, partner involvement, and student enthusiasm, while the hindering factor was limited time allocation. Overall, the management of P5 adhered to guidelines without significant obstacles.